Upaya Pengasuh dalam Membantu Menerapkan Perilaku Disiplin pada Anak (Studi Kasus di Panti Asuhan Salib Putih Salatiga) - Ika Wulansari; Ajeng Ayu Widiastuti; Tritjahjo Danny Soesilo (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Satya Wacana, 2018)
This study aims to find out how caregivers in helping children to develop or build discipline from an early age conducted by 3 caregivers of the Orphanage of the White Cross on the Orphanage Children of the White Cross especially against one early childhood. The type of this research is descriptive qualitative with case study method, data collection by interview and data analysis with qualitative. In this study there are 3 subjects that help one child in building discipline. The results of the study show that the discipline of children is increasing from previously unattended discipline until now already have good discipline, in building discipline. The way in which the subject tends to be different from the other caregivers. Subjects do not use corporal punishment and it is done in a better way. The way the subject tends to be a subtle way with good advice, real stories, habits, good examples, daily schedules made, gift giving to children.